2011
DOI: 10.1111/j.1476-5381.2011.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin interacting protein is a novel mediator of retinal inflammation and neurotoxicity

Abstract: BACKGROUND AND PURPOSEUp-regulation of thioredoxin interacting protein (TXNIP), an endogenous inhibitor of thioredoxin (Trx), compromises cellular antioxidant and anti-apoptotic defences and stimulates pro-inflammatory cytokines expression, implying a role for TXNIP in apoptosis. Here we have examined the causal role of TXNIP expression in mediating retinal neurotoxicity and assessed the neuroprotective actions of verapamil, a calcium channel blocker and an inhibitor of TXNIP expression. EXPERIMENTAL APPROACHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 60 publications
(90 reference statements)
8
64
0
1
Order By: Relevance
“…In other studies, inhibition of TXNIP expression by verapamil has also been reported (48), but this effect has been extended to other calcium channel blockers and inhibitors such as diltiazem and NiCl 2 , as well as with calcium chelator EGTA. This suggests that this inhibition of TXNIP function is perhaps not a direct effect of verapamil itself, but more likely due to a reduction in intracellular calcium concentrations (42).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, inhibition of TXNIP expression by verapamil has also been reported (48), but this effect has been extended to other calcium channel blockers and inhibitors such as diltiazem and NiCl 2 , as well as with calcium chelator EGTA. This suggests that this inhibition of TXNIP function is perhaps not a direct effect of verapamil itself, but more likely due to a reduction in intracellular calcium concentrations (42).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that TRX levels may be a useful marker of oxidative stress in a variety of disorders [17]. Previous studies also suggested serum TRX levels as indicator of inflammation [18] and immune dysregulation [19]. These findings indicated that TRX may be a useful marker of stroke.…”
Section: Introductionmentioning
confidence: 90%
“…In NMDA-induced neuronal injury or death, excessive Ca 2þ influx and subsequent activation of Ca 2þ -dependent responses, including formation of nitric oxide (NO) via neuronal NO synthase (NOS) (Morizane et al, 1997;Vorwerk et al, 1997), are thought to be important events. In addition, upregulation of inflammatory proteins and recruitment of leukocytes into the retina are involved (Nakazawa et al, 2007;Al-Gayyar et al, 2011). Furthermore, reductions in retinal blood flow may be an additional cause of progression of the ischemic retinal damage, because damage to the retinal microvasculature was observed in these experimental models of retinal neurodegeneration (Zheng et al, 2007;Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 97%